1991
DOI: 10.1172/jci115392
|View full text |Cite
|
Sign up to set email alerts
|

Rapid alteration in circulating free thyroxine modulates pituitary type II 5' deiodinase and basal thyrotropin secretion in the rat.

Abstract: TSH secretion is decreased by both T4 and T3. This negative feedback control of TSH secretion has been correlated with an increase in pituitary nuclear T3 content, and it is not clear whether T4 exerts its effect directly on the thyrotroph or after its deiodination to T3. However, levels of the pituitary enzyme catalyzing T4 to T3 conversion, 51)-II, are decreased in the presence of an increased amount of T4. Thus, it is unclear why the thyrotroph would have a mechanism for modulating the production of T3, if … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

1995
1995
2016
2016

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(14 citation statements)
references
References 29 publications
(28 reference statements)
0
14
0
Order By: Relevance
“…Despite one study [26] suggesting that both T4 and T3 might act directly on the pituitary gland to inhibit TSH secretion, most authors consider that T3, more so than T4, exerts its inhibitory effect on TSH secretion. This could explain why the TSH in the HISe group was lower at the end of the trial, potentially due to a more potent inhibitory effect of T3 on the pituitary gland.…”
Section: Selenium and Iodine Status Of The Cowsmentioning
confidence: 99%
“…Despite one study [26] suggesting that both T4 and T3 might act directly on the pituitary gland to inhibit TSH secretion, most authors consider that T3, more so than T4, exerts its inhibitory effect on TSH secretion. This could explain why the TSH in the HISe group was lower at the end of the trial, potentially due to a more potent inhibitory effect of T3 on the pituitary gland.…”
Section: Selenium and Iodine Status Of The Cowsmentioning
confidence: 99%
“…Recently, it was demonstrated that T4 also appears to have a direct effect on TSH suppression (Abend et al 1991). Triac also suppressed TSH secretion in humans (Mechelany et al 1991, Sherman & Ladenson 1992, Bracco et al 1993) but exhibited substantial thyromimetic effects.…”
Section: Administration Of T2 In Rat Pituitary Fragmentsmentioning
confidence: 99%
“…Nonetheless, the intrinsic homeostatic nature of D2 weakens the argument for its proposed major role in the TSH feedback mechanism (10). It is well known that low-serum T 4 increases D2 activity and that high T 4 concentrations do the opposite (11).…”
mentioning
confidence: 99%